Reorganization of Effective Geographical Factors on National Power - Yar, Fayaz Gul Mazloum; Ihsan, Ihsan Ullah; Baidar, Karim Ullah (International Law Discourse in Southeast Asia, 2024)
A group of human beings produced the nation and founded the states, and political organizations have the power. All physical and spiritual capabilities that existed in the particular political and geographical territory can be called ‘national power’. National power has different sources and bases, which are considered to be the elements of ‘national power’. The issue of national power has been attracting the attention of geographers, geopolitical specialists, and global communication experts. Each group has introduced the elements for the ‘national power’. This academic and research article will help to recognize the effects of geographical factors on ‘national power’. In addition to this, the purpose of this research is to identify the elements and sources of ‘national power’. We have investigated those geographical factors that are highly affecting ‘national power’. The methodology of data collection for this particular research is library research. Many great, international, and reliable resources have been used and cited in this academic article and research. The result of this research states that, besides the other crucial factors for national power, geographical factors also play a very vital role in national power. Such geographical factors and their effects can be used to measure and get to know the power of countries or states. The importance of this research is knowing how countries benefit from the existence of geographical facilities and features of national and global power.